2013
DOI: 10.4103/0022-3859.118033
|View full text |Cite
|
Sign up to set email alerts
|

Eschar in scrub typhus

Abstract: The eschar is the most useful diagnostic clue in patients with acute febrile illness in areas endemic for Scrub typhus and therefore should be thoroughly examined for its presence especially over the covered areas such as the groin, genitalia, infra-mammary area and axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 4 publications
2
48
0
Order By: Relevance
“…In this study, it was found that the eschar was mainly confined to the trunk, inguinal, genital and axially areas of the patients. Similar pattern distribution was observed in studies carried out in India [9] which also revealed a significant difference in the distribution of eschars between males and females. While the location of eschars is common on the chest and abdomen among females, the axilla, groin and genitalia areas were more common in males.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was found that the eschar was mainly confined to the trunk, inguinal, genital and axially areas of the patients. Similar pattern distribution was observed in studies carried out in India [9] which also revealed a significant difference in the distribution of eschars between males and females. While the location of eschars is common on the chest and abdomen among females, the axilla, groin and genitalia areas were more common in males.…”
Section: Discussionsupporting
confidence: 88%
“…12 A necrotic eschar which is considered as most useful diagnostic clue for scrub typhus was present in 46(45%) cases of our study population similar to a study done in Taiwan though it was reported as high as 86.3% in some study and also as low as 5%. [13][14][15] In our present study the commonest site of eschar was inguinal region 18%, followed by trunk and axilla, similar to the study by Jamil. 16 Few patients had eschar in the inframammary region and one had penile eschar.…”
Section: Discussionsupporting
confidence: 78%
“…In females it was primarily present in the chest and abdomen (42.3%), while in males it was present in the axilla, groin and genitalia (55.8%). Unusual sites of eschar were reported to be in the cheek, ear lobe and dorsum of the feet [32] . Five to eight days after the onset of fever, a macular or maculopapular rash may appear on the trunk and later extend to the arms and the legs in a small proportion of patients [31] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In a large retrospective analysis of 418 patients with confirmed scrub typhus and an eschar, a significant difference in the distribution of eschar was noted between males and females [32] . In females it was primarily present in the chest and abdomen (42.3%), while in males it was present in the axilla, groin and genitalia (55.8%).…”
Section: Clinical Featuresmentioning
confidence: 99%